Regulatory Mechanism of MicroRNA-9 / Long Non-Coding RNA XIST Expression on Mouse Macrophage RAW264.7 Apoptosis Induced by Oxidized Low Density Lipoprotein. Issue 2 (1st February 2022) - Zhang, Xiaoling; Wang, Si; Cai, Yuyan; He, Weihong; Yang, Qing; Li, Chen
ABSTRACT: It aims to analyze the influential mechanism of microRNA-9 (miR-9) and long non-coding RNA XIST (lncRNA XIST) expression on the proliferation and apoptosis of macrophages induced by oxidized-low density lipoprotein (ox-LDL). Firstly, lncRNA XIST overexpression vector was constructed, and then RAW264.7 cells were used as the research object. Methylthiazolyl tetrazolium (MTT) method, flow cytometry, and Western blot were used to detect and compare the differences of cell proliferation, apoptosis, and the expression levels of apoptosis signal-regulating kinase 1 (ASK1), c-Jun N-terminal kinase (JNK), matrix metalloproteinase-9 (MMP-9), and B-cell lymphoma-2 (Bcl-2) after ox-LDL induction and transfection of miR-9 mimic, miR-9 inhibitor and XIST expression vector, respectively. The results showed that lncRNA XIST overexpression vector was successfully constructed and transfected into cells, wh5ich can inhibit the expression level of miR-9. Compared with the normal control group, ox-LDL can inhibit cell proliferation, promote cell apoptosis, and increase the expression level of target protein. Moreover, transfection of XIST expression vector based on ox-LDL induction can significantly enhance the inhibition of cell proliferation, and promote cell apoptosis and the expression of target protein. Transfection of miR-9 mimic can improve the biological changes induced by ox-LDL. After co-transfection of miR-9 mimic and XIST expression vector based on ox-LDL induction, cell proliferation, apoptosis, and target protein expression level were not significantly different from those induced by ox-LDL alone. In summary, the increased expression level of miR-9 can inhibit the apoptosis of macrophages induced by ox-LDL. lncRNA XIST can positively regulate the apoptosis of macrophages induced by ox-LDL.